Which expression is equivalent to 2x2 + 2x + 4? (2x - 1)(x + 4) (2x + 1)(x - 4) C (2x + 1)(x + 4) None of these​

Respuesta :

Answer:

  • D. None of these​

Step-by-step explanation:

Given expression:

  • 2x² + 2x + 4

Answer options for equivalent expression:

A. (2x - 1)(x + 4)= 2x² + 8x - x - 4 = 2x² + 7x - 4

  • Incorrect

B. (2x + 1)(x - 4) = 2x² - 8x + x - 4 = 2x² - 7x - 4

  • Incorrect

C. (2x + 1)(x + 4) = 2x² + 8x + x + 4 = 2x² + 9x + 4

  • Incorrect

D. None of these​

  • Correct